Screening diagnostic candidates from Leishmania infantum proteins for human visceral leishmaniasis using an immunoproteomics approach - Lage, Daniela P.; Ludolf, Fernanda; Silveira, Patrícia C.; Machado, Amanda S.; Ramos, Fernanda F.; Dias, Daniel S.; Ribeiro, Patrícia A. F.; Costa, Lourena E.; Vale, Danniele L.; Tavares, Grasiele S. V.; Martins, Vívian T.; Chávez-Fumagalli, Miguel A.; et al. (Parasitology, 2019)
There is no suitable vaccine against human visceral leishmaniasis (VL) and available drugs are toxic and/or present high cost. In this context, diagnostic tools should be improved for clinical management and epidemiological evaluation of disease. However, the variable sensitivity and/or specificity of the used antigens are limitations, showing the necessity to identify new molecules to be tested in a more sensitive and specific serology. In the present study, an immunoproteomics approach was performed in Leishmania infantum promastigotes and amastigotes employing sera samples from VL patients. Aiming to avoid undesired cross-reactivity in the serological assays, sera from Chagas disease patients and healthy subjects living in the endemic region of disease were also used in immunoblottings. The most reactive spots for VL samples were selected, and 29 and 21 proteins were identified in the promastigote and amastigote extracts, respectively. Two of them, endonuclease III and GTP-binding protein, were cloned, expressed, purified and tested in ELISA experiments against a large serological panel, and results showed high sensitivity and specificity values for the diagnosis of disease. In conclusion, the identified proteins could be considered in future studies as candidate antigens for the serodiagnosis of human VL.